Legal aspects of the licensee's obligations according to the Creative Commons licenses and their relationship to copyright - Dr. Maen Mohammed Amin Ali Alqudah (Taez University, 2023)
The topic of the Creative Commons licenses is very important nowadays because this license is new and different from the traditional licenses. The aim of this research article is to address the legal aspects of a licensee's obligations according to the Creative Commons licenses and their relationship to copyright. The Creative Commons licenses raise several questions that this study will focus on answering, namely: the concept of the Creative Commons licenses, the characteristics of the Creative Commons licenses, the licensee's obligations under the Creative Commons licenses, and the relationship between the Creative Commons licenses and copyrights. The importance of this research article comes from the fact that Creative Commons licenses are a new mechanism and an unconventional type of license over copyright. The problem of this study lies in the author's fear of infringement of his exclusive rights after granting the Creative Commons licenses to others. Finally, in this study, an analytical and descriptive research methodology was used to clarify the ambiguities in the legal aspects of the licensee's obligations under the Creative Commons licenses and their relationship to copyright. In the conclusion of this study many important results and recommendations are communicated.